2018
DOI: 10.3201/eid2403.161275
|View full text |Cite
|
Sign up to set email alerts
|

Cache Valley Virus inAedes japonicus japonicusMosquitoes, Appalachian Region, United States

Abstract: We detected Cache Valley virus in Aedes japonicus, a widely distributed invasive mosquito species, in an Appalachian forest in the United States. The forest contained abundant white-tailed deer, a major host of the mosquito and virus. Vector competence trials indicated that Ae. j. japonicus mosquitoes can transmit this virus in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…albopictus and Ae. japonicus [17][18][19][20]. The principal vector is unknown, but vector competence studies and field isolations have shown that Anopheles quadrimaculatus and An.…”
Section: Introductionmentioning
confidence: 99%
“…albopictus and Ae. japonicus [17][18][19][20]. The principal vector is unknown, but vector competence studies and field isolations have shown that Anopheles quadrimaculatus and An.…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated an interaction between detectable CVV infection in mice following a challenge and exposure to mosquitoes (Edwards et al, ). Eight studies investigated determinants of vector competence such as dose, extrinsic incubation period, infection rate, dissemination rate and transmission rate under experimental conditions (Aitken & Spence, ; Ayers et al, ; Blackmore et al, ; Miller, ; Reeves & Miller, ; Saliba et al, ; Yang, Chan, et al, ; Yuill & Thompson, ).…”
Section: Resultsmentioning
confidence: 99%
“…The Bunyamwera serogroup was created in 1960 by grouping together related viruses demonstrating some level of cross‐reactivity (Casals & Whitman, ). Currently, recognized CVV subtypes include Tlacotalpan and Playas, identified in Mexico and Ecuador, respectively (Armstrong, Andreadis, & Anderson, ; Blitvich, Lorono‐Pino, Garcia‐Rejon, Farfan‐Ale, & Dorman, ; Yang, Chan, et al, ). Similar viruses, such as Maguari and Xingu, have been categorized as genomically distinct from CVV (Armstrong et al, ; Blitvich, Lorono‐Pino, et al, ; Dunn, Pritlove, & Elliott, ; Groseth et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cinereus, Culex pipiens, and some other species activity cycles have been studied in Sweden because of the transmission of Ockelbo disease (caused by Sindbis virus) and tularaemia in Sweden [6]. Aedes mosquitoes are vectors of these and many other diseases [2,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%